A Meta-Regression Analysis of Consumer Willingness to Pay for Aquaculture Products. (1st August 2022) - Smetana, Kerri; Melstrom, Richard T.; Malone, Trey
Abstract: This article uses meta-regression analysis to examine variation in willingness to pay (WTP) for farm-raised seafood and aquaculture products. We measure the WTP premiums that consumers have for common product attributes and examine how WTP varies systematically across study design elements, populations of interest, and sample characteristics. Based on metadata from 45 studies, the meta-regression analysis indicates that WTP estimates differ significantly with the availability of attributes such as domestic and environmental certification, but also with sample income and gender representation.